(untitled) (Nexo Revista Científica, 2020)
The management of natural disasters requires understanding their essence, making accurate assessments, planning, and providing appropriate solutions. The purpose of this study is to evaluate the physical resilience of the 22 neighborhoods of Babol located in the north of Iran against earthquakes. The methodology of this applied research study is descriptive-analytical. In this regard, by initially studying similar national and international studies, using the expert opinion of seismology and urban planning specialists and interviewing experienced urban managers in the field of crisis management, 30 effective indices on physical resilience against earthquake risk were extracted. Then, using analytic functions of GIS software and multi-criteria models including AHP, TOPSIS, VIKOR and COPRAS, the physical resilience of Babol against earthquakes was evaluated. Then, in order to obtain accurate results, using the integration models including the Statistic, BORDA and COPELAND, the physical resilience of Babol’s 22 neighborhoods was evaluated. The analysis of the final GIS maps shows that neighborhoods 2, 3, 4, 5, and 11 have very high physical resilience and neighborhoods 6, 8, 10, 12 and 14 have very low physical resilience against earthquakes.